2020
DOI: 10.1515/humor-2019-0052
|View full text |Cite
|
Sign up to set email alerts
|

“If we don’t quarrel, we joke”: Emic perspectives on Belarusian families’ humorous folklore

Abstract: The paper discusses Belarusian couples’ reflections on the role of humorous folklore in their daily family interactions. The interviewees generally regarded being humorous as a positive feature and identified (explicitly or implicitly) several functions of humor, such as framing group boundaries, offering criticism, and sharing ideas that would otherwise be difficult to communicate. A recurring distinction evoked by respondents was between “good” (benevolent) and “bad” (offensive) humor. However, interviews al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The affect of the family environment can be seen on the level of humour appreciation (Wilson et al 1977) and accounts for the existence of family humour styles (Everts 2003). As I have argued elsewhere (Fiadotava 2018;2020a;2020c), family humour is always tightly connected to the personal experiences of family members, and its performances add new layers to the relationship between the performer and their audience. Family units share many features with other informal groups (for example, groups of friends) when it comes to humorous communication.…”
Section: T H E O R E T I C a L B A C K G R O U N D A N D L I T E R A T U R E O V E R V I E Wmentioning
confidence: 99%
“…The affect of the family environment can be seen on the level of humour appreciation (Wilson et al 1977) and accounts for the existence of family humour styles (Everts 2003). As I have argued elsewhere (Fiadotava 2018;2020a;2020c), family humour is always tightly connected to the personal experiences of family members, and its performances add new layers to the relationship between the performer and their audience. Family units share many features with other informal groups (for example, groups of friends) when it comes to humorous communication.…”
Section: T H E O R E T I C a L B A C K G R O U N D A N D L I T E R A T U R E O V E R V I E Wmentioning
confidence: 99%
“…Teasing is used to achieve a range of relational goals (e.g., enjoyment, flirting, conversation initiation; Beck et al, 2007; Mills, 2018) and fosters closeness in both developing (Haugh & Pillet-Shore, 2018) and established (Fiadotava, 2021) relationships. In face-to-face communication, teasing is experienced as better-intentioned amid greater common ground, such as between friends versus acquaintances (Buglass et al, 2020; Gorman & Jordan, 2015; Jones et al, 2005).…”
Section: Teasing Through Textingmentioning
confidence: 99%
“…It also provided us with a selection of humour examples that people share with their friends and family. The study of self-reported humour can provide insights into how and why people use or avoid certain types and topics of humour (Fiadotava 2021). Relying on self-reported accounts of humour also helps to understand that emic perspectives on forms and topics of humour can be very different from researchers' perspectives (ibid.…”
Section: A T a A N D M E T H O D Smentioning
confidence: 99%